A Zone-Based Self-Organized Handover Scheme for Heterogeneous Mobile and Ad Hoc Networks - Murad Khan; Kijun Han (International Journal of Distributed Sensor Networks)
Uninterrupted internet services are need of the day and their demand will increase in future by manifold. However, providing uninterrupted services under heterogeneous networks environment is a challenging task. One of the major challenges in this regard is the management of handover system between various networks. This paper proposes a handover management scheme by dividing the total coverage area of the base station (BS) or access point (AP) into three different zones (strong, average, and weak zones), respectively, on the basis of receive signal strength indication (RSSI) to provide fast vertical handover support in heterogeneous wireless networks. Furthermore, a new event is proposed and added to the IEEE 802.21: media independent handover (MIH) standard to integrate the functionality of multithreshold. The proposed scheme is implemented in NS2 and it is shown that our scheme provides a superior performance over the previous methods used for similar purposes.